Based on ZrO2/graphene/ZrO2 Q-switched mid-infrared Er3+:ZBLAN fiber laser. (24th January 2019) - Zhang, Wei; Ju, Yao; Ning, Shougui; Wang, Shutong; Yang, Chao; Zhang, Hong; Feng, Guoying; Zhou, Shouhuan
Abstract: ZrO2 nanoparticles with an average size of ~40 nm are prepared by an electrical arc discharge method. Here, we fabricated a saturable absorber mirror (SAM) by spin-coating ZrO2, graphene and ZrO2 onto a homemade high-reflective mirror. Stable Q-switching operation in Er 3+ :ZBLAN fiber laser is achieved by using the as-prepared ZrO2 /graphene/ ZrO2 SAM. Compared with ZrO2 SAM, the ZrO2 /graphene/ZrO2 SAM has a lower Q-switching threshold and wider range of repetition rates. The maximum average output power of 285 mW is obtained with the repetition rate of 106.61 kHz, pulse width of 0.908 µ s and timing jitter of 0.514% at the pump power of 4.84 W by using the ZrO2 /graphene/ ZrO2 SAM.